Toolkits for 21st century teaching: Practical implications for the 4th industry skills development - Md Zamin, Ainul Azmin (Penerbit UITM, 2017)
What are the super skills for the 21st Century? Can the skills be taught deliberately in classrooms? How will the teachers deliver their lessons effectively for the present generation? Toolkits For The 21st Century Learning: Practical Implications For the 4th Industry Skills Development is a comprehensive book and reference guide for teachers who wish to equip their students with the 10 super skills in order to survive the current and future challenges. The book is ideal for all educators, teachers, lecturers and practitioners who are engaged in improving and preparing their students for the 4th Industrial Revolution. The result of an innovative and collaborative work, this book provides the perfect combination of theoretical discourse, pedagogical recommendations and practical solutions that helps teachers, practitioners, lecturers and educators derive maximum benefit from its content. Each chapter is organized in four central sections; an introduction of the skill, the underlying theories behind it, several recommendations on how to position the skill in education and two lesson plans as an added value. The reader can use the lesson plan simply by following the steps provided or adapt them to suit the needs of their learners. This book is a commendable effort from twenty lecturers from various higher learning institutions all over Malaysia. The pioneers of UiTM/ UKM TESL degree holders draw on more than two decades of teaching experience with their talent in academic writing to produce this reference book as a torch for a clear explanation and effective teaching. This book is an invaluable reading for those who wish to strategize their teaching using integrated methods that can enhance student engagement and improve learning outcomes.